The Construction of MSMES by the Agency of Industry, Trade and Cooperatives of North Aceh Regency - Muryali Muryali; Nurhafni Nurhafni; Aiyub Aiyub; Ahmad Yani (Master Program of Sociology, Universitas Malikussaleh,, 2021)
MSMEs in North Aceh Regency are very instrumental in helping to overcome problems of poverty and unemployment. The role of the government in the empowerment of MSMEs is expected through coaching. Each MSME has its own potential in developing its business. This MSME needs to be built with the aim to motivate new and old entrepreneurs to be creative in accordance with their respective business fields. This research aims to find out how the construction and obstacles are experienced by the Ministry of Industry, Trade and Cooperatives of North Aceh Regency. In this study use qualitative with deskriftive methods. Research was conducted in North Aceh Regency, the informant was determined by purposive sampling. Data collection with wawancar, documentation studies and skilling. The results showed that the development of MSMEs in North Aceh Regency by the relevant Agency had not been carried out in accordance with expectations, this was due to the lack of professionals owned by the agency. Less participation from MSMEs in improving the ability related to ways to run their business in the modern and digital era.